Epidemiology of hepatitis B virus infection in the Republic of Moldova - Petru Iarovoi, Constantin Rimis, Constantin Spinu, Maria Isac (The Journal of Infection in Developing Countries, 2008)
Background: The Republic of Moldova is considered a high endemic country with hepatitis B virus infection having a prevalence of AgHBs of 8 % and higher. This paper describes the epidemic process and changes in the acute hepatitis B incidence in Moldova from 1966 until 2006. The objective was to evaluate the prophylactic measures that have led to the decline in the epidemic process of this infection. Methodology: Epidemiological analysis of the surveillance data on acute hepatitis B incidence in the Republic of Moldova was conducted. The data were obtained from the national reporting system of infectious diseases. Results: In the course of hepatitis B virus infection evolution in the Republic of Moldova, the epidemic process had both increasing and decreasing phases; however, starting in 1989 the incidence of this infection decreased from 66.4 to 7.5 per 100,000 population in 2006. The decrease of the incidence has been most significant in children under 15 years, dropping from 80.8 to 2.0 per 100,000 population in the mentioned period. Conclusions: Data collected in the Republic of Moldova shows that vaccination against hepatitis B virus infection may be a very efficient preventive measure and may have a positive impact on reducing the morbidity of this infection.